Bone marrow sinusoidal endothelium as a facilitator/regulator of cell egress from the bone marrow. (May 2019) - Hassanshahi, Mohammadhossein; Hassanshahi, Alireza; Khabbazi, Samira; Su, Yu-Wen; Xian, Cory J.
Graphical abstract: Bone marrow sinusoidal endothelial cells constitutively provide adhesion molecules such as E-selectin, P-selectin, ICAM-1, and VCAM-1 to the cells within the bone marrow which have corresponding ligands by which the egress of cells from bone marrow into the circulation might be facilitated/regulated. Apart from expressing adhesion molecules, bone marrow sinusoidal endothelial cells regulate egress of bone marrow residing cells by providing chemokines including CXCL1, CXCL2, and CXCL12, and also by providing ECM proteins including collagen IV, laminin, fibronectin, hemonectin, hyaluronic acid, thrombospondin, and tenascin to the egressing cells. Abstract: Despite more attention to cell migration from circulation into the bone marrow (BM), particularly homing of haematopoietic stem/progenitor cells, the process and mechanisms of cell mobilisation from the BM into the circulation remain largely underexplored. The process of cell mobilisation or transcellular cell migration from BM into the circulation (cell egress) is a crucial biological process in mammals as it is important to maintain homeostasis of various physiological functions including, but not limited to, the immune system, erythropoiesis, platelet release, and stem cell migration. The BM microvascular system composes of a monolayer of specialized endothelial cells, called sinusoidal endothelial cells (SECs). While it is very well evident that the process of cell egress occurs exclusively through BM SECs, there is a lack of systematic analyses addressing the extent of contribution of BM SECs to the process of cell egress from the BM. Therefore, this review aims to address the potential ability of BM SECs in regulating and/or facilitating the process of cell egress from BM. In this review, we address, firstly, the unique ultra-/structural and molecular features of BM SECs and discuss the possible biological interactions between BM SECs and various egressing cells in physiological conditions. Secondly, we propose the potential role of BM SECs in egress of leukemic cells from BM into the circulation. Finally, we discuss the potential role of BM SECs in homing of haematopoietic stem cells. Collectively, the current review suggests that the BM SECs may not be merely a neutral gatekeeper for cell intravasation and extravasation, but rather is a dynamic trafficking surveillance system, thereby the process of BM cell egress/mobilisation can be regulated.